AgNO3 spray method for measurement of chloride penetration: the state of art - Real, L. V.; Oliveira, D. R. B.; Soares, T.; Medeiros, M. H. F. (Revista ALCONPAT, 2015)
The durability of the buildings has been evaluated through visual inspections associated with field and laboratory tests. Nowadays, for analysis of the carbonation colorimetric method by spraying phenolphthalein is widely used, due to the ease and high reliability. However, when there is the presence of chlorides, the tests are long and expensive. As an alternative, there is a colorimetric method (AgNO3). The method is easy to use, low cost and allows for on-site reviews. But when there is presence of carbonation, the analysis becomes more complex, since reducing the pH and leads to discoloration of the concrete. This paper presents studies on the use of the colorimetric method for evaluation of the depth of chloride penetration in concrete. There is no consensus in academic circles as to eliminate this influence and to determine the turning point, however there is research demonstrating the influence of cement type on the colorimetric method. Keywords: concrete; corrosion; chloride penetration; silver nitrate; colorimetric method.